Experimental investigation of thermal vehicular environment during the summer season. (2nd January 2022) - Danca, Paul; Bode, Florin; Meslem, Amina; Croitoru, Cristiana; Sandu, Mihnea; Nastase, Ilinca; Lungu, Catalin; Batali, Loretta
Abstract : Thermal comfort evaluation for vehicle occupants is very complicated due to the transient nature and non-uniformity of the vehicle interior. The thermal sensation of an automobile occupant is affected by the surrounding environment. Furthermore, the existing standard was developed for steady state and controlled conditions and it utilizes three evaluation indices, some of which are not adapted for this complex environment. In this article, the three standardized indices are compared in terms of thermal comfort, for a passenger vehicle in summer season. The results show that the mean values of the PMV/PPD model calculated at a single point with Comfort Sense equipment are far from the TSV mean values which were collected in questionnaires, while the teq index which was calculated with an advanced thermal manikin are closer to the TSV comfort votes. This may be explained by the fact that the TSV and teq consider the sensation for each body part at the local level. For a correct evaluation of the thermal comfort in non-uniform and transient environments like in vehicles, it is not enough to measure a single point.